2011
DOI: 10.1007/s11239-011-0554-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-world practices to prevent venous thromboembolism with pharmacological prophylaxis in US orthopedic surgery patients: an analysis of an integrated healthcare database

Abstract: Major orthopedic surgery patients are at high risk of venous thromboembolism (VTE) in-hospital and post-discharge. This study assessed real-world inpatient and outpatient thromboprophylaxis practices following knee or hip arthroplasty. Patients from the Henry Ford Health System aged ≥18 years undergoing knee and hip arthroplasty (January 1997-June 2007) were identified using Current Procedural Terminology codes from administrative databases. Patients with <18 months of continuous enrollment in the system's hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Rates of compliance to CPGs recommendations are typically described between 40 and 54% [5,16,18]. However, in a study carried out by Merli et al, adherence to CPG was reported to be around 12% [19]. Compliance to CPGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of compliance to CPGs recommendations are typically described between 40 and 54% [5,16,18]. However, in a study carried out by Merli et al, adherence to CPG was reported to be around 12% [19]. Compliance to CPGs.…”
Section: Discussionmentioning
confidence: 99%
“…This program included: 1. Definition of performance indicators, 2. establishment of a baseline of the rate of compliance (February 2012), 3. implementation of improvement strategies [17][18][19], and 4. systematic monitoring of performance indicators (February 2012 to August 2014).…”
Section: Methodsmentioning
confidence: 99%
“…These results are consistent with a recent study by Merli et aI., in which an increase in the lengthof prophylaxis duration was observedover the years from 2 to 4 days between 1997 and 2005 and to 115 (9.0)days in 2007. 20 The 8th edition of the ACCP guidelines recommends continuing thromboprophylaxisfor up to 35 daysin patients undergoing hipreplacement or hip fracture surgery, as wellas those undergoing knee replacement surgery.' In a meta-analysis,extended-duration thromboprophylaxis of 30-42 days was associated with significant reduction in the likelihood of symptomatic DVTIPE compared withstandard-duration thromboprophylaxis in patientsundergoing elective totalhip or knee replacement (OR 0.38; 95% CI 0.24 to 0.61),without an increased riskof major bleeding," Furthermore, extended-duration thromboprophylaxis has been found to be cost-effective, because increased pharmacy costs wereoffset by reductions in DVTIPE eventsand theassociated costs of'hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The use prophylactic anticoagulant agents is one of the most effective strategies to prevent the onset of venous thromboembolism following major orthopedic surgery (1)(2)(3)(4). However, thromboprophylaxis has been associated with an increased risk of major bleeding, intracranial bleeding and fatal bleeding (5-7).…”
Section: Introductionmentioning
confidence: 99%